Hope, coping skills, and the prefrontal cortex in alcohol use disorder recovery. (3rd September 2017) - Bradshaw, Spencer D.; Shumway, Sterling T.; Dsauza, Cynthia M.; Morris, Neli; Hayes, Nicholas D.
ABSTRACT: Background : Alcohol use disorders adversely affect individual and societal health. These disorders are a chronic brain disease, and protective factors against relapse should be studied. Prefrontal cortex (PFC) dysfunction is evident in alcohol use disorders, and research that explores recovery of the PFC in alcohol use disorders is needed, specifically in regard to how psychological and behavioral factors can augment medicalized treatments and protect against relapse. For example, hope or a belief that recovery is possible is an important cognitive construct—thought to precede behavioral action—that has been associated with relapse. Objectives : In this study, associations between healthy coping skills and hope (psychological/behavioral factors) and PFC regional activation in response to alcohol cue exposure were examined. It was also examined whether such associations were unique to alcohol cues. Methods : Forty-two participants, 32 males and nine females in recovery from an alcohol use disorder (AUD), were administered a subjective hope and coping in recovery measure. They also viewed alcohol, positive, negative, and neutral cues during functional near-infrared spectroscopy (fNIR) PFC assessment. Results : Levels of healthy coping skills positively correlated with activation in the right dorsomedial prefrontal cortex (DMPFC) in response to alcohol cues. This finding was unique to alcohol cues. Conclusion : The association between coping skills and activation of the right DMPFC in response to alcohol cues may reflect greater action restraint and top-down PFC control processing that may protect against relapse.